Sonication of Removed Hip and Knee Prostheses for Diagnosis of Infection - Trampuz, Andrej; Piper, Kerryl E; Jacobson, Melissa J; Hanssen, Arlen D; Unni, Krishnan K; Osmon, Douglas R; Mandrekar, Jayawant N; Cockerill, Franklin R; Steckelberg, James M; Greenleaf, James F; Patel, Robin (The New England journal of medicine, 2007)
Current techniques for the identification of the infecting organism in prosthetic-joint (e.g., hip or knee) infection remain insensitive. In this study of 331 surgeries involving prosthetic joint replacement, a new technique that sonicates the removed artificial joint is found to be more sensitive in identifying the infecting organism than are standard culture techniques. In surgeries involving prosthetic joint replacement, a new technique that sonicates the removed artificial joint is found to be more sensitive in identifying the infecting organism than are standard culture techniques. In the United States, 638,000 patients underwent hip or knee replacement in 2003. 1 Although they may improve the quality of life, these procedures are associated with complications, including aseptic failure and prosthetic-joint infection. 2 It is important to distinguish prosthetic-joint infection from other causes of joint failure, because its management is different. 3 Nonmicrobiologic methods developed for diagnosing native-joint infection use different criteria from those used to diagnose prosthetic-joint infection. 4 Microbiologic diagnosis of prosthetic-joint infection may also require different criteria from those used for the microbiologic diagnosis of native-joint infection. Most clinicians and laboratory workers culture periprosthetic tissue (hereafter referred to as . . .